A Study on Digital Mentoring-Next Generation Research Strategies and Suggestions - Rekha Gupta (AG Volumes, 2022)
For today’s competitive environment, the classic concept of a mentor—someone who helps or advises a less-experienced and frequently younger person—needs to be both updated and enlarged. It’s a good fit for today’s youngsters, who are technologically sophisticated and spend a lot of time online, to utilise digital tools for mentoring since they fit their profile well. As the first digital and iPod generation, people who were born between 1980 and 1995 are known as Millennials. A similar phrase has been used to these individuals, who have been dubbed "digital natives" for their complete dependence on technology in their daily lives. In fact, millennials have never known a world without the Internet or personal computers. Using means that are already known to the children, digital mentoring has a big opportunity to reach them. Mentoring tools for both mentors and mentees may be accessed at any time and from any location thanks to the universal advantages of transcending temporal and physical constraints. Youth mentoring organisations throughout the world may benefit from sharing resources and ideas over the internet. Mentors are able to contact with mentors regardless of location or time. At any one moment, they may converse with up to three mentees simultaneously. A broad variety of digital applications are now accessible to meet the requirements of a wide spectrum of people, including online mentors.